Teaching outside of the box: a short-term international internship for pre-service and in-service physical education teachers. Issue 3 (4th May 2017) - Robinson, Daniel B.; Barrett, Joe; Robinson, Ingrid
Abstract: This article reports on results from a qualitative study of a two-week international internship for pre-service and in-service physical education (PE) teachers in a developing nation (Belize). Relying upon data from questionnaires that were administered before and after the short-term international internship, participants' perspectives related to their professional and personal development were investigated. Understanding the overlap that necessarily exists between professional and personal growth, five themes are identified and discussed. These include: (1) Kids are Kids (Or are they?), (2) Relationships Matter, (3) Cooperation and Collaboration in Teaching: Learning Together, (4) Teaching without Bells and Whistles, and (5) Recognising One's Own Privilege. In light of these findings, some suggestions for future practice and inquiry are offered.